The Impact of Family Environment on the Social and Emotional Development of Children of Working Parents: A Study of Muzaffarpur District : कामकाजी माता-पिता के बच्चों के सामाजिक एवं संवेगात्मक विकास पर पारिवारिक वातावरण का प्रभाव: मुजफ्फरपुर जिले का एक अध्ययन - Kumari, Sandhya; Kumari, Kusum (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study analyzes the impact of the family environment on the social and emotional development of children of working parents in Muzaffarpur district. As parents—especially mothers—are becoming more active in professional life, the processes of childcare and upbringing are also undergoing changes. The research adopted a descriptive survey method. A total of 120 children (aged 8 to 12 years) were included in the study, with an equal number of boys and girls, all having working parents. The findings reveal significant differences in children’s emotional security, social behavior, and parental involvement, depending on family structure, parents’ work schedules, and availability. This study suggests strategies to strengthen family relationships and ensure balanced development of children in dual-income households. Abstract in Hindi Language: यह अध्ययन मुजफ्फरपुर जिले में कामकाजी माता-पिता के बच्चों के सामाजिक और भावनात्मक विकास पर पारिवारिक वातावरण के प्रभाव का विश्लेषण करता है। जैसे-जैसे माता-पिता, विशेषकर माताएं, कामकाजी जीवन में अधिक सक्रिय होती जा रही हैं, वैसे-वैसे बच्चों के पालन-पोषण की प्रक्रिया में भी बदलाव आ रहे हैं। इस शोध में वर्णनात्मक सर्वेक्षण विधि अपनाई गई। कुल 120 बच्चों (8 से 12 वर्ष) को शोध में शामिल किया गया, जिनमें लड़के और लड़कियां समान संख्या में थे और सभी के माता-पिता कार्यरत थे। अध्ययन के निष्कर्ष बताते हैं कि बच्चों के भावनात्मक सुरक्षा, सामाजिक व्यवहार और अभिभावकों की सहभागिता में परिवार की संरचना, माता-पिता के कार्यकाल और उपलब्धता के आधार पर महत्वपूर्ण अंतर देखने को मिला। यह शोध पारिवारिक संबंधों को मजबूत करने और दोहरी आय वाले परिवारों में बच्चों के संतुलित विकास के लिए आवश्यक रणनीतियाँ सुझाता है। Keywords: पारिवारिक वातावरण, कामकाजी माता-पिता, सामाजिक विकास, भावनात्मक विकास